Social Mobility through Education: Lifelong Learning and the Roma-Minority in Selected Central and Eastern European Countries - Óhidy, Andrea (Central European Journal of Educational Research, 2023)
Education plays a central role in supporting or impeding social mobility (Bourdieu & Passeron, 1974; Fend, 1980, 2006). The disadvantaged social and economic situation of the biggest part of the Roma minority (not only) in Central and Eastern Europe is usually seen as the main reason for their low educational attainment and success. And vice versa: the poor educational results are considered the main reason for their social deprivations. Therefore, education and lifelong learning have become the main strategy for improving their situation, especially since the ´Europeanization of the Roma issue` (Ram, 2015) through the European Union. Today, Education and lifelong learning are now the centre of EU-policies for achieving political and economic goals, like economic growth and social cohesion (Óhidy, 2008, 2009). This article analyzes the problems faced by and opportunities presented to the Roma people in selected Central and Eastern European countries, problems and opportunities arisen in the years up until 2020, regarding social mobility through education. In its analysis, this paper focused on the similarities. The article is based on 5 country studies from 2019, written by experts from the Czech Republic, Hungary, Poland, Romania and Slovakia (see Óhidy & Forray, 2019). The study uses the evidence from the country studies from Markéta Levínska, Dana Bittnerová & David Doubek, 2019 (Czech Republic), Julianna Boros & Eszter Gergye, 2019 (Hungary), Agnieszka Swietek & Wiktor Osuch, 2019 (Poland), Aurora Adina Colomeischi, 2019 (Romania) and Rastislav Rosinsky, 2019 (Slovakia) to explore the similarities in challenges, to increase the participation and success of Roma people.